HP improves application versatility, productivity, workflow efficiency for large-format customers. IN Gadgets Monthly.
New solutions help PSPs take advantage of high-value digital pages in the sign and display market.
Keywords: Hewlett-Packard Company; Hewlett-Packard Ltd; Marketing -- Technological innovations; Print service providers (PSPs).; HP Scitex; Hostert Automatic Loader